Technical and Economic Analysis of Floating PV System for Putra Mosque in Malaysia - Khan M.R.B.; Pasupuleti J.; Jidin R. (Institute of Electrical and Electronics Engineers Inc., 2023)
This paper proposes the design of a hybrid renewable energy generation system (HRES) for a large mosque. The selected location is the Putra Mosque, Putrajaya, Malaysia, as it represents a typical large mosque in the country. The location has promising results for the installation of a floating PV system based on the available area on the 12 km lake. Hence, the primary goal of this study is to conduct technical and economic analysis for an installation of a grid-connected floating Photovoltaic (PV) system to mitigate dependency in grid power and minimize CO2 emission. The overall RE system components modeled for the location comprises PV, converter, battery storage, and grid. Whereas, the data collected includes load profile and renewable resources such as solar radiation and temperature. Hybrid Optimization Model for Electrical Renewable (HOMER) software was used to model and simulate the optimal configuration of the hybrid system. The results show a 5-kW grid-connected floating PV system is the best configuration with an initial capital of $27,894 and NPC of $482,723. This configuration has a 3% RE fraction. This system has lower initial capital and NPC compared to other configurations and has a higher RE energy mix leading to lower CO2 emission 2020 IEEE.